Enhancing International Partnership in the Egyptian Pre-university Education: Perspectives of International Organizations - Rizk, Ayman (Journal of Interdisciplinary Studies in Education, 2020)
The purpose of this article is to present the perspectives of international officials regarding partnerships between the Egyptian Ministry of Education and international organizations. Data of this article were gathered mainly from semi-structured interviews with twelve international organizations’ officials in Egypt. The article suggests that international organizations working on the pre-university education face serious challenges that undermine their efforts and affects the efficiency of their contributions and initiatives in a very negative way. It concludes with a set of recommendations that can be considered by the Egyptian Government for enhancing its international partnerships in education.